2003
DOI: 10.1002/ejoc.200300391
|View full text |Cite
|
Sign up to set email alerts
|

Acidity of Substituted Benzenes − An Ab Initio Study of the Influence of Methoxy, Trifluoromethyl and Trifluoromethoxy Groups by a Novel Trichotomy Formula

Abstract: Keywords: Acidity / Aromaticity / Electrostatic field effect / Substituent effectsThe acidities of mono-and polysubstituted benzenes incorporating one, two, or three OCH 3 , OCF 3 , or CF 3 groups were investigated by use of reliable ab initio theoretical models. The calculated deprotonation energies are in very good agreement with available experimental data, although these are unfortunately sparse. A recently developed novel trichotomy formula proved useful for interpretation of predicted variation in acidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…The ortho -(trifluoromethoxy)benzenide ion ( 74 ) has been evaluated at the MP2(fc)/6-311+G**//HF/6-31+G* level of theory. Most conformers were found to populate a flat valley that extends from the syn -periplanar to the perpendicular arrangement, and only thereafter the free energy rises slowly to attain a 1.7 kcal/mol maximum at the anti -periplanar state. ,
…”
Section: 3 Conformational Preferences and Mobilitymentioning
confidence: 96%
See 2 more Smart Citations
“…The ortho -(trifluoromethoxy)benzenide ion ( 74 ) has been evaluated at the MP2(fc)/6-311+G**//HF/6-31+G* level of theory. Most conformers were found to populate a flat valley that extends from the syn -periplanar to the perpendicular arrangement, and only thereafter the free energy rises slowly to attain a 1.7 kcal/mol maximum at the anti -periplanar state. ,
…”
Section: 3 Conformational Preferences and Mobilitymentioning
confidence: 96%
“…Its charge-attenuating effect is long-ranging, leveling off only moderately when the substituent is shifted from the ortho through the meta to the para position of the carbanion (Table ). When two or three trifluoromethoxy groups are present in the same molecule, their individual contributions to the overall acidity are essentially additive (Table ) 7 MP-2 ab Initio Proton Affinities of Trifluoromethoxy-Substituted Benzenides Relative to the Phenyl Anion a OCH 3 + 0.5 −1.4 −9.2 −20.2 −20.1 OCF 3 −9.5 −10.9 −16.8 −35.7 −46.0 CF 3 −10.1 −10.7 −13.7 −27.6 −38.5 a Δ H Prot 400.0; all numbers in kcal/mol …”
Section: 34 Aromatic Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…This computational procedure yields acidities which compare reasonably well with experiment and much more demanding G2 method. [27][28][29][30][31] We have shown that a very useful tool for interpretation of acidities is provided by the triadic formula: 26,32,33 PAðA…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…[1,2] At the same time, it is a relatively bulky substituent. [3] Early attempts to metalate (trifluoromethyl)benzene with butyllithium in refluxing diethyl ether proved regiochemically unclean, affording, after trapping with dry ice, a 100:40:1 mixture of 2-, 3-and 4-(trifluoromethyl)benzoic acid in moderate yield (33-48 %).…”
Section: Introductionmentioning
confidence: 99%